The hydromorphometric characteristics of the Arab river basin in Lattakia - Syria using GIS and DEM (Latakia University Journal -Basic Sciences Series, 2023)
A hydromorphometric database was built for the Arab River Basin based on DEM, and using the GIS 10.5 program and by adopting its tools in the hydrological analysis /Spatial analyst / Hydrology/, with the aim of providing decision makers in the water field with the data necessary for an integrated water management. The study of the basin showed that it is one of the sinuous rivers, with a parallel drainage network, and compatible with alluvial and clay deposits with light slope. The Arab River basin occupies a triangular area of ​​56.99 km2 and a meandering circumference of 41.45 km. The Arab River Basin is characterized by a low form factor, medium elongation, light slope, low relief index and ruggedness, and a coarse topographic texture, and accordingly the river is in its youthful stage. The length of the river drainage network was /94.43 km/ arranged in 5 orders according by Strahler, which consisted of /155/ streams with high frequency of streams, and with a strong and inverse correlation coefficient between the degree of the order and the number of its streams amounted to 95%, and the control of flows to the west at a rate of /24.5%/. Regressive erosion prevailed and the basin widened, in addition to an increase in surface run-off and a decrease in water infiltration with low drainage density and a high coefficient of infiltration.